Some Algorithms for the Error Linear Complexity of Binary 2(n)-Periodic Sequences - Chang, Zuling; Wang, Xueyuan; Duan, Li (Wuhan University journal of natural sciences, 2013)
Based on the Games-Chan algorithm and StampMartin algorithm, this paper provides some new algorithms to compute the error linear complexity spectrum of binary 2(n)-periodic sequences. These new algorithms are clearer and simpler than old algorithms, and they can quickly compute the error linear complexity spectrum of sequences according to different situations. We also discuss such algorithms and give some new results about linear complexity and error linear complexity of sequences.